Penerapan Kesehatan dan Keselamatan Kerja (K3) di Masa Pandemi Covid-19 pada Proyek Pembangunan Gedung OJK KR. 4 Jawa Timur - Athallah Prawira Bima Nursandah; Wateno Oetomo; Michella Beatrix (Faculty of Engineering, Kadiri University, 2022)
The success of a construction is influenced by the performance of workers. Worker performance is influenced by the environment to the existing occupational safety and health system. The Covid pandemic has had an impact on changing the structure of the construction sector, one of which is on workers. These changes are not easily implemented by construction workers. There are several factors that cause it is not easy to apply such as understanding, ability and attitude. The purpose of this study is to analyze the application of occupational health and safety (K3) in the construction project of the OJK KR.4 building, East Java, Surabaya. Data obtained from questionnaires distributed to workers. The data obtained were then analyzed for Validity, Reliability, Normality, and Multiple Linear Regression including the F-Test, Coefficient of Determination, and T-Test. The results showed that the COVID-19 pandemic and OSH behavior had an effect on the implementation of OSH by 74.4% and the remaining 25. 6% influenced by other things. However, the attitude and behavior of K3 became the most dominant among the two variables studied. So that knowing the most influential variables in the implementation of K3 during a pandemic can inform construction organizations and policy makers about aspects to implement preventive measures aimed at protecting construction workers.